2022
DOI: 10.1038/s41598-022-14696-8
|View full text |Cite
|
Sign up to set email alerts
|

A network analysis reveals the interaction between fear and physical features in people with neck pain

Abstract: Although neck pain is known to be a complex and multifactorial condition characterised by the interplay between physical and psychological domains, a comprehensive investigation examining the interactions across multiple features is still lacking. In this study, we aimed to unravel the structure of associations between physical measures of neuromuscular function and fear of movement in people with a history of neck pain. One hundred participants (mean age 33.3 ± 9.4) were assessed for this cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…A recent study by Devecchi et al [28] also observed that kinesiophobia was the most relevant factor associated with the kinematic features of patients with neck pain, supporting the fear-avoidance model, which considers fear of motion as a potential driver for physical deconditioning and a mediator between pain and disability in people with neck pain [46].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A recent study by Devecchi et al [28] also observed that kinesiophobia was the most relevant factor associated with the kinematic features of patients with neck pain, supporting the fear-avoidance model, which considers fear of motion as a potential driver for physical deconditioning and a mediator between pain and disability in people with neck pain [46].…”
Section: Discussionmentioning
confidence: 70%
“…These results agree with previous research that also observed that kinesiophobia showed stronger associations with kinematic measures of neck movement than pain intensity or disability did [ 45 ]. A recent study by Devecchi et al [ 28 ] also observed that kinesiophobia was the most relevant factor associated with the kinematic features of patients with neck pain, supporting the fear-avoidance model, which considers fear of motion as a potential driver for physical deconditioning and a mediator between pain and disability in people with neck pain [ 46 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, a network analysis has the potential to identify and quantify interactions between various signs and symptoms in people with WAD, better exposing the potential complexity of these interactions. This type of analysis has been implemented to investigate other patient populations, such as those with tension-type headaches or other chronic pain conditions, providing evidence on the interaction between different variables and highlighting potential future targets for pain management (Devecchi et al, 2022; Fernández-de-Las-Peñas Significance: Through two network analyses, we evaluated the interaction between pain-related factors, fear of movement, neck disability and physical factors in people who had experienced a whiplash injury. We demonstrated that physical factors may be involved in the maintenance and development of chronic pain after a whiplash injury.…”
Section: Introductionmentioning
confidence: 99%
“…The association between single features, typically achieved by assessing simple correlations, may not capture the complexity of spinal pain, including WAD (Falla & Hodges, 2017; Ludvigsson et al, 2016). In contrast, a network analysis is an approach that can be applied to examine the interaction between multiple factors, including psychological features, measures of physical function and patient‐reported outcome measures (PROMs), since it can be used to quantitatively assess and graphically describe multiple interactions (Devecchi et al, 2022). Indeed, the analysis of the interaction between physical and psychological factors has a stronger association with pain intensity and disability than the presence of either factor alone in people with neck pain (Johnston et al, 2010).…”
Section: Introductionmentioning
confidence: 99%